RISE IN COSMETIC SURGERY AMONG TEENAGERS - Qoraboyeva Dilnoza Xursanali’s daughter, (TADQIQOTLAR, 2026)
Abstract. This article explores the growing trend of cosmetic surgery among teenagers and examines the factors influencing this increase. In recent years, cosmetic procedures have become more accessible and socially acceptable, especially among young people. Through analysis of existing research, surveys, and student perspectives, this study investigates how social media, peer pressure, and changing beauty standards shape teenagers’ attitudes toward cosmetic surgery. The findings suggest that while some  teenagers  seek  procedures  for  medical  or  reconstructive  reasons,  many  are influenced  by  unrealistic  beauty  ideals  and  online  comparisons.  The  study  also highlights  psychological  and  social  implications,  including  issues  related  to  self-esteem, identity formation, and mental health.